2019
DOI: 10.1007/s40415-019-00519-0
|View full text |Cite
|
Sign up to set email alerts
|

Graphene quantum dots-induced physiological and biochemical responses in mung bean and tomato seedlings

Abstract: Different physiological and biochemical responses in mung bean (Vigna radiata L.) and tomato (Solanum lycopersicum L.) seedlings induced by graphene quantum dots (GQDs) (250-1500 mg L −1) were studied. Results showed that both seeds exposed to GQDs can still germinate normally. However, the growth of the seedlings after germination was adversely affected by the GQDs, and mung bean was more sensitive than tomato. In hydroponic experiments, the appropriate concentration of GQDs enhanced the accumulation of chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 51 publications
5
14
0
Order By: Relevance
“…Iron-NPs were also shown to enhance proline content of grapevine under control and salinity conditions [ 31 ]. This enhancement was reported following QD application, as well [ 45 ], in accordance with the current study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Iron-NPs were also shown to enhance proline content of grapevine under control and salinity conditions [ 31 ]. This enhancement was reported following QD application, as well [ 45 ], in accordance with the current study.…”
Section: Discussionsupporting
confidence: 93%
“…Exogenous application of PAs decreased MDA levels in plants under salinity [ 24 , 26 , 27 , 44 ]. Furthermore, graphene QD application at low doses decreased MDA content [ 45 ]. Mozafari et al [ 31 ] observed similar mitigating effect of iron-NPs on decreasing MDA content of grapevine under salinity.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous application of PAs decreased MDA levels in plants under salinity [24,26,27,44]. Furthermore, graphene QD application at low doses decreased MDA content [45]. Mozafari et al [31] observed similar mitigating effect of iron-NPs on decreasing MDA content of grapevine under salinity.…”
Section: Discussionmentioning
confidence: 86%
“…In terms of the effect of nanomaterials, iron-NPs enhanced APX, SOD and POD enzymatic activities of grapevine under salinity conditions [31]. Feng et al [45] reported enhanced CAT activity at lower graphene QD concentration, likely due to enhanced oxidative stress that reduces biosynthesis of antioxidant enzymes like CAT. Gohari et al [12,13] reported positive effect of MWCNTs-COOH and TiO 2 NPs on SOD, CAT, APX and GP enzymatic activities under both control and salt stress conditions, in line with the current nding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation